2004
DOI: 10.1245/aso.2004.11.912
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Remove True Sentinel Nodes Can Cause Failure of the Sentinel Node Biopsy Technique: Evidence from Antimony Concentrations in False-Negative Sentinel Nodes from Melanoma Patients

Abstract: We have recently found that antimony (originating from the technetium 99m antimony trisulfide colloid, used for preoperative lymphoscintigraphy) can be measured in tissue sections from archival paraffin blocks of sentinel nodes (SNs) by means of inductively coupled plasma mass spectrometry (ICP-MS) to confirm that removed nodes are true SNs. We performed a retrospective analysis of antimony concentrations in all our false-negative (FN) SNs to determine whether errors in lymphadenectomy (i.e., failure to remove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…Although the overlap of modalities increases the accuracy of the test, technical difficulties may be encountered at any of these stages. Surgical removal of incorrect nodes or missing micrometastases on histopathological sections are examples of simple technical errors [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the overlap of modalities increases the accuracy of the test, technical difficulties may be encountered at any of these stages. Surgical removal of incorrect nodes or missing micrometastases on histopathological sections are examples of simple technical errors [22].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, antimony levels in the SN and the positive node from the neck dissection were measured. This was based on earlier studies demonstrating that antimony (originating from the antimony sulphide colloid used for preoperative LS) is retained in high levels in archival paraffin blocks of SNs and is absent or present only in very small quantities in non-SNs removed from the same regional node field at the same operation [22,23]. The original SN had an antimony level of 3.747 ppb, whereas the positive node from the neck dissection had a level of only 0.0015 ppb suggesting that the correct node was excised at the time of SNB.…”
Section: Casementioning
confidence: 99%
“…The measurement of antimony levels in paraffinembedded pathological specimens is a novel technique used with an inductively coupled plasma mass spectrometer after microwave heat treatment that can be used to confirm SLN identity [3]. The procedure was used in an earlier study to retrospectively analyse the antimony levels of 'SLN' tissue in patients who subsequently went on to develop a nodal recurrence in the lymphatic field despite a negative SLNB result [4]. Here, it was shown that seven of the 27 nodes ultimately demonstrated metastasis on review and in five of the 27 cases a nonsentinel node had been harvested at surgery and had erroneously been designated as 'SLNs'.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that concentrations of antimony (originating from the technetium 99 m antimony trisulfide colloid used for preoperative lymphoscintigraphy at our center) can be measured in tissue sections from archival paraffin blocks and that this can confirm whether the nodes removed and submitted as SNs were true SNs [43,44]. Antimony levels in tissue sections of archival tissue from 20 of the false negative SNs were measured using inductively coupled plasma mass spectrometry (ICP-MS) and were found to be very low in 5 of 20 presumed SNs [45]. This strongly suggests that failure to remove the true SN may have been the cause of the false negative SN biopsy in these five patients.…”
Section: What Methodology Is Employed For Pathologicmentioning
confidence: 99%